Footscray cemetery register and memorial inscriptions burial register 1860-1970 and memorial inscriptions to c1996 - Genealogical Society of Victoria; Church of Jesus Christ of Latter-Day Saints. Footscray Ward. (Melbourne : Genealogical Society of Victoria, 2008)
"This DVD contains indexes which draw on the Footscray cemetery burial register 1860-1970, copying of which was kindly allowed by the cemetery authorities some years ago; and transcriptions of memorials in the Footscray Cemetery to circa 1996 published by the GSV in 1998. One index of names in the burial register and in the transcriptions has been built by GSV volunteers, with each name hyperlinked to the relevant source. Read more about the transcriptions of the memorials and see a map of the cemetery on page three. Knowing if there is more than one person buried in the same grave, and if other relevant burials are in adjacent grave(s), is of genealogical value, and two other indexes are included to enable this question to be examined."--Introduction.
Footscray Cemetery headstone transcriptions / transcribed and typed by members of the Footscray ward of the Church of Jesus Christ of the Latter-Day Saints.
System requirements: DVD drive, Adobe Reader version 8 or later.
Digital content preserved
Keywords: Footscray Cemetery (Vic.); Cemeteries -- Victoria -- Footscray; Victoria -- Genealogy -- Databases; Footscray (Vic.) -- Genealogy; Melbourne (Vic.) -- Genealogy